Dari Kasih Menjadi Luka Kekerasan Rumah Tangga dan Gugurnya Hak Orang Tua - Romansyah Fitra Lebie; Nur Mohamad Kasim; Dolot Alhasni Bakung (Lembaga Pengembangan Kinerja Dosen, 2025)
This paper aims to explore the legal basis and ethical reasoning for the revocation of parental rights due to domestic violence by placing the child's best interests as a compass and mapping the gap between norms and judicial practices. The method used is normative-doctrinal legal research based on a literature review of the Domestic Violence Law, the Marriage Law, the Child Protection Law, selected jurisprudence, and scientific literature, analyzed qualitatively through systematic interpretation, argument construction, and linking to the facts of the impact of domestic violence on children. The results show that positive law provides a firm basis for sanctions and protections including restrictions on interaction and revocation of custody rights, but implementation is often hampered by vague evidence of psychological violence, the victim's economic dependence, and weak execution of alimony; revocation effectively breaks the cycle when accompanied by a protection order, a post-decision parenting plan, and ongoing psychosocial support. Policy implications include guidelines for proving coercive control, expanding access to timely protection orders, integrating trauma-informed services in religious courts, and a mechanism for executing alimony that does not burden victims, with schools, community health centers, and communities as early detection nodes. Ultimately, legal work and social networks converge in one simple goal: that home again means a safe place for children to return.